2016
DOI: 10.14740/jocmr2369w
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Morphometrical Study of the Human Ossicular Chain: A Review of the Literature and a Meta-Analysis of Experience Over 50 Years

Abstract: The ossicular chain has been known for 500 years and yet there are a small number of morphometrical studies. We reviewed the whole literature that is available online regarding the human ossicular chain from an anatomist perspective and correlated the data from all the papers that showed any relevance. Inclusion and exclusion criteria were developed a priori. A thorough description of all ossicular differences has been made and we present their variations in dimensions trying to associate measurements obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…In this study, we investigated middle ear development during the fetal period (CRL between 37 and 197 mm) using high‐resolution MRI. Our findings indicated that the MEOs are morphologically similar during fetal development and adulthood (Bast and Anson, ; Anson and Donaldson, ; Unur et al, ; Noussios et al, ). However, dynamic calcification and endochondral ossification of cartilage were observed as patchy, low‐density areas on MR images during the observation period.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In this study, we investigated middle ear development during the fetal period (CRL between 37 and 197 mm) using high‐resolution MRI. Our findings indicated that the MEOs are morphologically similar during fetal development and adulthood (Bast and Anson, ; Anson and Donaldson, ; Unur et al, ; Noussios et al, ). However, dynamic calcification and endochondral ossification of cartilage were observed as patchy, low‐density areas on MR images during the observation period.…”
Section: Discussionsupporting
confidence: 64%
“…The total maximum lengths of the malleus, incus, and stapes in five samples exhibiting a CRL between 145 and 197 mm in the present study were comparable to those observed in newborns and adults. Previous studies have reported the total lengths of the malleus, incus, and stapes as 7.69 ± 0.60, 6.47 ± 0.55, and 3.22 ± 0.31 mm in newborns (Unur et al, ) and as 7.80 ± 0.33, 5.36 ± 1.23, and 3.25 ± 0.10 mm in adults (Noussios et al, ), respectively. Such morphometric data may indicate that growth of MEOs nearly ceases when the fetus has attained a CRL of approximately 150 mm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Knowledge of the ossicular chain's complex anatomy is important for hearing research and surgical procedures concerning the middle ear. The ossicular chain is known to vary naturally in humans (Kamrava & Roehm, 2017) and can present with congenital malformations (Noussios, Chouridis, Kostretzis, & Natsis, 2016); however, more information on its variation across the population is needed for better understanding of normal and pathological function.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis revealed that relatively few morphological or morphometrical studies have been done on the ossicular chain over the past 50 years, and in these studies the method of analysis and morphometrical results varied greatly (Noussios et al, 2016). While older studies relied on publishing morphometrical measurements to study ossicle shape and orientation (Kamrava & Roehm, 2017; Noussios et al, 2016), newer imaging technologies allow for three‐dimensional (3D) model derivation from two‐dimensional (2D) image slices, providing much greater detail on ossicle structure and function. Initial studies producing 3D models of the ossicular chain used low‐resolution, clinical computed‐tomography (CT) images to create models.…”
Section: Introductionmentioning
confidence: 99%